2005
DOI: 10.1016/s1570-7946(05)80001-x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the mixed integer dynamic optimisation of waste water treatment plants using scenario-dependent optimal control

Abstract: In many real life processes, operational objectives, constraints and the process itself may change over time. This is due to changing product requirements, market demands and other external or internal influences, which constitute a certain scenario. Modelbased techniques can provide optimal solutions to the corresponding scheduling and process control problems. This paper focuses on those situations, where the objectives and constraints of plant operation depend on the scenario and therefore change over time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Other application studies have been reported, e.g. by Singh et al [50] and Johansen and Sbar-baro [51] for blending processes and by Busch et al [52] for a waste-water treatment plant.…”
Section: General Idealmentioning
confidence: 94%
“…Other application studies have been reported, e.g. by Singh et al [50] and Johansen and Sbar-baro [51] for blending processes and by Busch et al [52] for a waste-water treatment plant.…”
Section: General Idealmentioning
confidence: 94%